2018
DOI: 10.1007/s11769-018-0938-6
|View full text |Cite
|
Sign up to set email alerts
|

Changing Connectivities of Chinese Cities in the World City Network, 2010–2016

Abstract: Against the backdrop of the sizable economic growth of China in recent years, this paper uses the most recent data gathering of the Globalization and World Cities (GaWC) research network to update and supplement earlier research on the shifting global connectivity of Chinese cities. The update consists of an evaluation of the connectivity of Chinese cities in 2016, the supplement of an analysis of the changing position of Chinese cities in the world city network between 2010 and 2016. To this end, we build on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Raźniak's [23] ranking of world economic centers proves Beijing's leading position in China's inland cities. Based on service firms' data gathering of Globalization and World Cities Study Group and Network [GaWC] research, Derudder [24] tracked the shifting global connectivity of Chinese cities between 2010 and 2016; this researcher found that most Chinese cities gained connectivity in the world urban networks due to the rise of the wholesale industry. In terms of China's urban networks, the most recent studies include that Xi [25] used online commodity services to reveal the spatial pattern of the national urban network under the influence of the internet economy, and Liang [26] mapped the international freight forwarding service regional network in the Yangtze River Delta.…”
Section: Inter-firm Investment and Inter-city Connectionsmentioning
confidence: 99%
“…Raźniak's [23] ranking of world economic centers proves Beijing's leading position in China's inland cities. Based on service firms' data gathering of Globalization and World Cities Study Group and Network [GaWC] research, Derudder [24] tracked the shifting global connectivity of Chinese cities between 2010 and 2016; this researcher found that most Chinese cities gained connectivity in the world urban networks due to the rise of the wholesale industry. In terms of China's urban networks, the most recent studies include that Xi [25] used online commodity services to reveal the spatial pattern of the national urban network under the influence of the internet economy, and Liang [26] mapped the international freight forwarding service regional network in the Yangtze River Delta.…”
Section: Inter-firm Investment and Inter-city Connectionsmentioning
confidence: 99%
“…Three factors which contributed to the area of containerization include “ productivity gain ,” “ container networks ” (Fremont, , pp. 431–442), and “ Connectivities ” (Derudder et al, , p. 183). Large E‐class container ships can be a major asset to Maersk and other shipping firms.…”
Section: Future Developments and Growth Prospectsmentioning
confidence: 99%
“…As the largest developing country in the world, China has experienced long-term and sustained ultra-high speed economic growth and large-scale urbanization since the implementation of reform and opening up in 1978 [2][3][4]. Chinese cities host many important innovative companies and their international connectivities are significantly growing in the world economy [5,6]. From 1989 to 2019, the urbanization rate rose from 26.21% to 60.60% [7], the newly added urban population was about 550 million, and the newly added urban built-up area was more than four times of the original urban area [8].…”
Section: Introductionmentioning
confidence: 99%